Electrokinetics in Earth Sciences: A Tutorial - L. Jouniaux; T. Ishido (International Journal of Geophysics)
We describe in this paper the theoretical background for the electrokinetics in rocks and in porous media, to be included in the special issue “Electrokinetics in Earth Sciences” of International Journal of Geophysics. We describe the methodology used for self-potential (SP) and for seismoelectromagnetic measurements, for both field and laboratory experiments and for modelling. We give a large bibliography on the studies performed in hydrology to detect at distance the water flow, to deduce the thickness of the aquifer and to predict the hydraulic conductivity. The observation of SP has also been proposed to detect fractures in boreholes, to follow the hydraulic fracturing, and to predict the earthquakes. Moreover, we detail the studies on geothermal applications.